Gene-to-metabolite networks for terpenoid indole alkaloid biosynthesis in Catharanthus roseus cells - Rischer, Heiko; Oresic, Matej; Seppänen-Laakso, Tuulikki; Katajamaa, Mikko; Lammertyn, Freya; Ardiles-Diaz, Wilson; Van Montagu, Marc C E; Inzé, Dirk; Oksman-Caldentey, Kirsi-Marja; Goossens, Alain (Proceedings of the National Academy of Sciences - PNAS, 2006)
Rational engineering of complicated metabolic networks involved in the production of biologically active plant compounds has been greatly impeded by our poor understanding of the regulatory and metabolic pathways underlying the biosynthesis of these compounds. Whereas comprehensive genome-wide functional genomics approaches can be successfully applied to analyze a select number of model plants, these holistic approaches are not yet available for the study of nonmodel plants that include most, if not all, medicinal plants. We report here a comprehensive profiling analysis of the Madagascar periwinkle (Catharanthus roseus), a source of the anticancer drugs vinblastine and vincristine. Genome-wide transcript profiling by cDNA-amplified fragment-length polymorphism combined with metabolic profiling of elicited C. roseus cell cultures yielded a collection of known and previously undescribed transcript tags and metabolites associated with terpenoid indole alkaloids. Previously undescribed gene-to-gene and gene-to-metabolite networks were drawn up by searching for correlations between the expression profiles of 417 gene tags and the accumulation profiles of 178 metabolite peaks. These networks revealed that the different branches of terpenoid indole alkaloid biosynthesis and various other metabolic pathways are subject to differing hormonal regulation. These networks also served to identify a select number of genes and metabolites likely to be involved in the biosynthesis of terpenoid indole alkaloids. This study provides the basis for a better understanding of periwinkle secondary metabolism and increases the practical potential of metabolic engineering of this important medicinal plant.